Overview of the Burden of Diseases in North Korea - Lee, Yo Han (The Korean Society for Preventive Medicine, 2013)
This article evaluates the overall current disease burden of North Korea through the recent databases of international organizations. It is notable that North Korea as a nation is exhibiting a relatively low burden from deaths and that there is greater burden from deaths caused by non-communicable diseases than from those caused by communicable diseases and malnutrition. However, the absolute magnitude of problems from communicable diseases like TB and from child malnutrition, which will increase the disease burden in the future, remains great. North Korea, which needs to handle both communicable and nutritional conditions, and non-communicable diseases, whose burden is ever more increasing in the nation, can now be understood as a country with the 'double-burden' of disease.